2020
DOI: 10.1002/cbf.3539
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiles of DNA methylation and differential gene expression in osteocytic areas from aged and young mice

Abstract: Altered DNA methylation upon ageing may result in many age‐related diseases such as osteoporosis. However, the changes in DNA methylation that occur in cortical bones, the major osteocytic areas, remain unknown. In our study, we extracted total DNA and RNA from the cortical bones of 6‐month‐old and 24‐month‐old mice and systematically analysed the differentially methylated regions (DMRs), differentially methylated promoters (DMPs) and differentially expressed genes (DEGs) between the mouse groups. Kyoto Encycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…However, there were differences among three mC contexts which might be related to differences in the sequences of different genetic elements ( Fang et al, 2017 ). Approximately 4.3% of cytosine sites were methylated, which is lower than the cortical bones in mice from 6.06 to 6.48% ( Wei et al, 2020 ). The highest proportion of CG methylation in this study was similar to that found in other species ( Wei et al, 2020 ) and tissues ( Li C. W. et al, 2015 ; Li J. X. et al, 2015 ; Zhang et al, 2018 ; Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, there were differences among three mC contexts which might be related to differences in the sequences of different genetic elements ( Fang et al, 2017 ). Approximately 4.3% of cytosine sites were methylated, which is lower than the cortical bones in mice from 6.06 to 6.48% ( Wei et al, 2020 ). The highest proportion of CG methylation in this study was similar to that found in other species ( Wei et al, 2020 ) and tissues ( Li C. W. et al, 2015 ; Li J. X. et al, 2015 ; Zhang et al, 2018 ; Tan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…Approximately 4.3% of cytosine sites were methylated, which is lower than the cortical bones in mice from 6.06 to 6.48% ( Wei et al, 2020 ). The highest proportion of CG methylation in this study was similar to that found in other species ( Wei et al, 2020 ) and tissues ( Li C. W. et al, 2015 ; Li J. X. et al, 2015 ; Zhang et al, 2018 ; Tan et al, 2020 ). Among the gene functional regions, TSSs presented the lowest methylation levels, which was consistent with the results in chickens’ liver ( Tan et al, 2020 ) and blood ( Zhang et al, 2018 ), but inconsistent in cortical bones of mice ( Wei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…Here, we analyzed cortical bone gene expression across four time points, the longest of which is older than prior analyses. (56,57) Relative to pairwise analysis of two time points, the continuous analysis of all four time points increased statistical power in identifying differentially expressed genes and revealed nine distinct temporal patterns of gene expression. Reassuringly, the results of pathway analysis using the pairwise and continuous approaches were largely similar and also correspond to prior analysis of gene expression in 19-week-versus 19-month-old mouse cortical bone, (56) with an age-dependent decrease in Wnt signaling and increase in immunomodulatory cytokine signaling.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, WGBS is at the forefront of epigenetic analysis and popularly utilized to investigate the genome-wide DNA methylation dynamics of mammalian developments [15] , [16] as well as the epigenetic marks of diseases [17] . But the bisulfite treatment converts unmethylated cytosine as thymine, reduces the complexity of reads, and thus causes a mapping challenge to aligners in WGBS [18] .…”
Section: Introductionmentioning
confidence: 99%